P205 The functionality of dating applications in sexual relationships and sexual health. (8th June 2017) - Vojt, Gabriele; Smith, Matthew; Woode-Owusu, Melvina; Mapp, Fiona; Flowers, Paul; Pothoulaki, Maria; Estcourt, Claudia; Palermo, Amir; Valencia, Mario; Ejedenawe, Oluwatomilayo; Dankyi, Stephanie; Attah, Sally-Rae; et al.
Abstract : Introduction: Dating apps are an increasing way people meet each other for sex and relationships. Their functionality captures aspects of contemporary sexual culture and reflects the ways relationships are understood. This study systematically assed dating app functionality in relation to sexual relationships and sexual health. Methods: We examined the top down-loaded 500 dating apps listed on a public platform of dating applications (App Annie). Following screening using inclusion and exclusion criteria, data were systematically extracted from included dating apps (n = 259). Data were collated regarding how the App functionality related to target population, and included links to sexual health interventions. We specifically coded how the Apps defined the kinds of relationship the app-user was in and the kind of relationship the app-user was looking for. Results: Forty percent of dating apps were designed for specific user populations defined by nationality, religion or sexual orientation and preference. Dating apps varied greatly in the ways their functionality reflected types of relationships (e.g, it's complicated', 'something long term', 'friends with benefits'). Only a minority of dating apps (4.2%) provided a link to sexual health information, interventions or referral to clinical service options. Discussion: This study can help clinicians to better understand the relationships people have, the words used to describe these relationships and the likely impact this has on sexual behaviours, onward transmission and potential partner notification interventions.